Idris proof by definition - proof

I can write the function
powApply : Nat -> (a -> a) -> a -> a
powApply Z f = id
powApply (S k) f = f . powApply k f
and prove trivially:
powApplyZero : (f : _) -> (x : _) -> powApp Z f x = x
powApplyZero f x = Refl
So far, so good. Now, I try to generalize this function to work with negative exponents. Of course, an inverse must be provided:
import Data.ZZ
-- Two functions, f and g, with a proof that g is an inverse of f
data Invertible : Type -> Type -> Type where
MkInvertible : (f : a -> b) -> (g : b -> a) ->
((x : _) -> g (f x) = x) -> Invertible a b
powApplyI : ZZ -> Invertible a a -> a -> a
powApplyI (Pos Z) (MkInvertible f g x) = id
powApplyI (Pos (S k)) (MkInvertible f g x) =
f . powApplyI (Pos k) (MkInvertible f g x)
powApplyI (NegS Z) (MkInvertible f g x) = g
powApplyI (NegS (S k)) (MkInvertible f g x) =
g . powApplyI (NegS k) (MkInvertible f g x)
I then try to prove a similar statement:
powApplyIZero : (i : _) -> (x : _) -> powApplyI (Pos Z) i x = x
powApplyIZero i x = ?powApplyIZero_rhs
However, Idris refuses to evaluate the application of powApplyI, leaving the type of ?powApplyIZero_rhs as powApplyI (Pos 0) i x = x (yes, Z is changed to 0). I've tried writing powApplyI in a non-pointsfree style, and defining my own ZZ with the %elim modifier (which I don't understand), but neither of these worked. Why isn't the proof handled by inspecting the first case of powApplyI?
Idris version: 0.9.15.1
Here are some things:
powApplyNI : Nat -> Invertible a a -> a -> a
powApplyNI Z (MkInvertible f g x) = id
powApplyNI (S k) (MkInvertible f g x) = f . powApplyNI k (MkInvertible f g x)
powApplyNIZero : (i : _) -> (x : _) -> powApplyNI 0 i x = x
powApplyNIZero (MkInvertible f g y) x = Refl
powApplyZF : ZZ -> (a -> a) -> a -> a
powApplyZF (Pos Z) f = id
powApplyZF (Pos (S k)) f = f . powApplyZF (Pos k) f
powApplyZF (NegS Z) f = f
powApplyZF (NegS (S k)) f = f . powApplyZF (NegS k) f
powApplyZFZero : (f : _) -> (x : _) -> powApplyZF 0 f x = x
powApplyZFZero f x = ?powApplyZFZero_rhs
The first proof went fine, but ?powApplyZFZero_rhs stubbornly keeps the type powApplyZF (Pos 0) f x = x. Clearly, there's some problem with ZZ (or my use of it).

The problem: powApplyI was not provably total, according to Idris. Idris' totality checker relies on being able to reduce parameters to structurally smaller forms, and with raw ZZs, this doesn't work.
The answer is to delegate the recursion to plain old powApply (which is proven total):
total
powApplyI : ZZ -> a <~ a -> a -> a
powApplyI (Pos k) (MkInvertible f g x) = powApply k f
powApplyI (NegS k) (MkInvertible f g x) = powApply (S k) g
Then, with a case split on i, powApplyIZero is proven trivially.
Thanks to Melvar from the #idris IRC channel.

powApplyI (Pos Z) i x doesn't reduce further because i is not in weak head normal form.
I don't have an Idris compiler, so I rewrote your code in Agda. It's pretty similar:
open import Function
open import Relation.Binary.PropositionalEquality
open import Data.Nat
open import Data.Integer
data Invertible : Set -> Set -> Set where
MkInvertible : {a b : Set} (f : a -> b) -> (g : b -> a) ->
(∀ x -> g (f x) ≡ x) -> Invertible a b
powApplyI : {a : Set} -> ℤ -> Invertible a a -> a -> a
powApplyI ( + 0 ) (MkInvertible f g x) = id
powApplyI ( + suc k ) (MkInvertible f g x) = f ∘ powApplyI ( + k ) (MkInvertible f g x)
powApplyI -[1+ 0 ] (MkInvertible f g x) = g
powApplyI -[1+ suc k ] (MkInvertible f g x) = g ∘ powApplyI -[1+ k ] (MkInvertible f g x)
Now you can define your powApplyIZero as
powApplyIZero : {a : Set} (i : Invertible a a) -> ∀ x -> powApplyI (+ 0) i x ≡ x
powApplyIZero (MkInvertible _ _ _) _ = refl
Pattern-matching on i induces unification and powApplyI (+ 0) i x becomes replaced with powApplyI (+ 0) i (MkInvertible _ _ _), so powApplyI can proceed further.
Or you could write this explicitly:
powApplyIZero : {a : Set} (f : a -> a) (g : a -> a) (p : ∀ x -> g (f x) ≡ x)
-> ∀ x -> powApplyI (+ 0) (MkInvertible f g p) x ≡ x
powApplyIZero _ _ _ _ = refl

Related

Haskell function composition - two one-dimensional functions to a two dimensional function

Let's assume I have a function f in Haskell, It takes a Double and returns a Double, and I have function g that also takes a Double and returns a Double.
Now, I can apply f to g like this: f . g.
Now, let's take a higher-dimensional function f, that
takes two Doubles and outputs one:
f :: Double -> Double -> Double
or
f :: (Double, Double) -> Double
And I have two g functions as well:
g1 :: Double -> Double, g2 :: Double -> Double
Now, I want to compose the functions to get something like:
composition x = f (g1 x) (g2 x)
Can this be achieved just by using the dot (.) operator?
You can make use of liftA2 :: Applicative f => (a -> b -> c) -> f a -> f b -> f c for this:
composition = liftA2 f g1 g2
Since a function is an applicative [src]:
instance Applicative ((->) r) where
pure = const
(<*>) f g x = f x (g x)
liftA2 q f g x = q (f x) (g x)
and liftA2 is implemented as [src]:
liftA2 :: (a -> b -> c) -> f a -> f b -> f c
liftA2 f x = (<*>) (fmap f x)
this will thus be resolved to:
liftA2 f g1 g2 x = (<*>) (fmap f g1) g2 x
= (fmap f g1 <*> g2) x
= (f . g1 <*> g2) x
= (\fa ga xa -> fa xa (ga xa)) (f . g1) g2 x
= (f . g1) x (g2 x)
= f (g1 x) (g2 x)
You can try this:
import Control.Arrow
composition = f . (g1 &&& g2)
(&&&) turns g1 :: a -> b and g2 :: a -> c into g1 &&& g2 :: a -> (b, c). Then you can apply normal composition.

How to prove that 2 is Prime in Idris?

I'm a beginner in Idris now, so I want to ask for help.
I have definition of division:
data DividesNat : (a : Nat) -> (b : Nat) -> Type where
Div : (k ** (k * x = y)) -> DividesNat y x
and definition of prime number, based on DividesNat:
data Prime : (p : Nat) -> Type where
ConsPrime : LTE 2 p ->
((d : Nat) -> DividesNat p d -> Either (d = 1) (d = p)) ->
Prime p
Now I want to prove that 2 is prime:
prf2IsPrime : Prime (S (S Z))
prf2IsPrime = ConsPrime (LTESucc (LTESucc LTEZero)) prf
where
prf : (d : Nat) -> DividesNat (S (S Z)) d ->
Either (d = 1) (d = (S (S Z)))
prf d x = ?prf_rhs
Cases with d = (S Z) or d = (S (S Z)) are pretty simple:
prf : (d : Nat) -> DividesNat (S (S Z)) d ->
Either (d = 1) (d = (S (S Z)))
prf Z (Div (x ** pf)) = ?prf_rhs2_3
prf (S Z) (Div (x ** pf)) = Left Refl
prf (S (S Z)) (Div (x ** pf)) = Right Refl
prf (S (S (S _))) (Div (x ** pf)) = ?rr_2
but I have no idea how to prove it for d = Z or d = (S (S (S _))). How can I show that these cases are impossible?
Finally I found the solution:
prf2IsPrime : Prime (S (S Z))
prf2IsPrime = ConsPrime (LTESucc (LTESucc LTEZero)) prf
where
prfGT32 : (S (S (S a))) `GT` (S (S Z))
prfGT32 = LTESucc (LTESucc (LTESucc LTEZero))
prf : (d : Nat) -> DividesNat (S (S Z)) d -> Either (d = 1) (d = (S (S Z)))
prf Z (Div (x ** pf)) = absurd (zeroIsNotDiv (x ** pf))
prf (S Z) (Div (x ** pf)) = Left Refl
prf (S (S Z)) (Div (x ** pf)) = Right Refl
prf (S (S (S _))) (Div (k ** pf)) =
absurd (gtIsNotDiv prfGT32 (k ** pf))

Can I extract a proof of bounds from an enumeration expression?

Consider this trivial program:
module Study
g : Nat -> Nat -> Nat
g x y = x - y
f : Nat -> List Nat
f x = map (g x) [1, 2 .. x]
It gives an obvious error:
|
4 | g x y = x - y
| ^
When checking right hand side of g with expected type
Nat
When checking argument smaller to function Prelude.Nat.-:
Can't find a value of type
LTE y x
— Saying I should offer some proof that this subtraction is safe to perform.
Surely, in the given context, g is always invoked safely. This follows from the way enumerations behave. How can I extract a proof of that fact so that I can give it to the invocation of g?
I know that I can use isLTE to obtain the proof:
g : Nat -> Nat -> Nat
g x y = case y `isLTE` x of
(Yes prf) => x - y
(No contra) => ?s_2
This is actually the only way I know of, and it seems to me that in a situation such as we have here, where x ≥ y by construction, there should be a way to avoid a superfluous case statement. Is there?
For map (\y = x - y) [1, 2 .. x] there needs to be a proof \y => LTE y x for every element of [1, 2 .. x]. There is Data.List.Quantifiers.All for this: All (\y => LTE y x) [1, 2 .. x].
But constructing and applying this proof is not so straight-forward. You could either build a proof about the range function lteRange : (x : Nat) -> All (\y => LTE y x) (natRange x) or define a function that returns a range and its proof lteRange : (x : Nat) -> (xs : List Nat ** All (\y => LTE y x) xs). For simplicity, I'll show an example with the second type.
import Data.List.Quantifiers
(++) : All p xs -> All p ys -> All p (xs ++ ys)
(++) [] ys = ys
(++) (x :: xs) ys = x :: (xs ++ ys)
lteRange : (x : Nat) -> (xs : List Nat ** All (\y => LTE y x) xs)
lteRange Z = ([] ** [])
lteRange (S k) = let (xs ** ps) = lteRange k in
(xs ++ [S k] ** weakenRange ps ++ [lteRefl])
where
weakenRange : All (\y => LTE y x) xs -> All (\y => LTE y (S x)) xs
weakenRange [] = []
weakenRange (y :: z) = lteSuccRight y :: weakenRange z
Also, map only applies one argument, but (-) needs the proof, too. So with a little helper function …
all_map : (xs : List a) -> All p xs -> (f : (x : a) -> p x -> b) -> List b
all_map [] [] f = []
all_map (x :: xs) (p :: ps) f = f x p :: all_map xs ps f
We can roughly do what you wanted without checking for LTE during the run-time:
f : Nat -> List Nat
f x = let (xs ** prfs) = lteRange x in all_map xs prfs (\y, p => x - y)

Can this function be implemented?

Is there any implementation for this function?
foo :: (Monad m, Monad n) => m a -> n a -> (a -> a -> a) -> m (n a)
foo x y f = ...
Yes, and it can be given a more general type.
foo :: (Functor f, Functor g) => (a -> b -> c) -> f a -> g b -> f (g c)
foo f fx gy = fmap (\x -> fmap (f x) gy) fx

What is a function composition algorithm that will work for multiple arguments, such as h(x,y) . f(x) . g(x) = h(f(x),g(x))?

For example, suppose we had the functions double(x) = 2 * x, square(x) = x ^ 2 and sum(x,y) = x + y. What is a function compose such as compose(compose(sum, square), double) = x^2 + 2*x? Notice that I'm asking a function that can be used for functions of any arity. For example, you could compose f(x,y,z) with g(x), h(x), i(x) into f(g(x), h(x), i(x)).
This is a common Haskell idiom, applicative functors:
composed = f <$> g1 <*> g2 <*> ... <*> gn
(A nicer introduction can be found here).
This looks very clean because of automatic partial application, and works like this:
(<*>) f g x = f x (g x)
(<$>) f g x = f (g x) -- same as (.)
For example,
f <$> g <*> h <*> i ==>
(\x -> f (g x)) <*> h <*> i ==>
(\y -> (\x -> f (g x)) y (h y)) <*> i ==>
(\y -> f (g y) (h y)) <*> i ==>
(\z -> (\y -> f (g y) (h y)) z (i z)) ==>
(\z -> f (g z) (h z) (i z)).
Applicative functors are more general, though. They are not an "algorithm", but a concept. You could also do the same on a tree, for example (if properly defined):
(+) <$> (Node (Leaf 1) (Leaf 2)) <*> (Node (Leaf 3) (Leaf 4)) ==>
Node (Leaf 4) (Leaf 6)
But I doubt that applicatives are really usable in most other languages, due to the lack of easy partial application.